2013
DOI: 10.1111/ijd.12115
|View full text |Cite
|
Sign up to set email alerts
|

Variety of complications after auricle piercing

Abstract: The fashion of body piercing is not safe. Complications after earlobe piercing are similar to those occurring in other sites of the auricle after piercing. Moreover, due to its prevalence, complications after earlobe piercing are statistically more common, which is why it is worth considering including earlobe piercing in the modern definition of body piercing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…11,16 Keloids following trauma especially ear piercing as in this study was reported by other authors. 8,11,18 The length of keloid was less than 5 cm in majority of the patients seen. This is similar to findings in another clinical study of keloid.…”
Section: Discussionmentioning
confidence: 91%
“…11,16 Keloids following trauma especially ear piercing as in this study was reported by other authors. 8,11,18 The length of keloid was less than 5 cm in majority of the patients seen. This is similar to findings in another clinical study of keloid.…”
Section: Discussionmentioning
confidence: 91%
“…Piercing practitioners were insufficiently aware of ear cartilage piercing complication. [ 19 ] In addition, operators of cosmetic shops, earring kiosks, and tattoo parlous may not be aware of the risks of ear piercing. In India, piercing is usually done by neighborhood barber, jeweler, or in beauty parlors.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma is the main complication of face-lift surgery: keloid formation after face-lift surgery has not been reported previously. 10 Indeed, periauricular incision is commonly used in face-lift surgery precisely because there is little movement in this region, which in turn reduces scar prominence and the risk of wound complications. Our patient did not have a history of keloids or family keloids.…”
Section: Discussionmentioning
confidence: 99%